Reputation: 2179
I am trying to find the modulo of an expression. All I know is that
(a+b) mod N = ((a mod N) + (b mod N)) mod N
How do I use it to simplify the following modulo operation?
(a - 2*b + 1) mod N
There must be some way to simplify it by considering it as
(a - b - b + 1) mod N ?
EDIT:
I have stumbled upon the following property too:
ab mod N = ((a mod N) (b mod N)) mod N
Will this be helpful somehow?
Upvotes: 0
Views: 7278
Reputation: 2288
If: (a+b) mod N = ((a mod N) + (b mod N)) mod N
then:
(a - 2*b + 1) mod N = ((a mod N) - (b mod N) - (b mod N) + (1 mod N)) mod N
It is simpler with large values of a and b and a small value for N.
For example: a=85773, b = 77733340, N=5: which would you rather solve
(85773 - 77733340 - 77733340 + 1) mod 5
or
((85773 mod 5) - (77733340 mod 5) - (77733340 mod 5) + (1 mod 5)) mod 5
for the second one i get (3 - 0 - 0 + 1) % 5 = 4
Upvotes: 1